Synergistic Effects of Nobiletin and Sorafenib Combination on Metastatic Prostate Cancer Cells. (17th November 2019) - Guney Eskiler, Gamze; Deveci, Asuman Ozkan; Bilir, Cemil; Kaleli, Suleyman
Abstract: Objective: Herein we, for the first time, investigated a potential synergistic effect of nobiletin (NOB) and sorafenib (SOR) on PC-3 prostate cancer and HUVEC control cell lines. Methods: In order to determine the cytotoxic and apoptotic effects of the combination of NOB and SOR, WST-1, Annexin V, and cell cycle analysis were performed. The potential molecular mechanism of apoptotic cell death was assessed by Bax, Bcl-2, CCDN1, Rb1, and CDKN1A gene expression and acridine orange (AO) and DAPI staining. Results: Our results indicated that NOB and SOR combination had a significant inhibitory effect on the viability of PC-3 cells with less toxicity on HUVEC cells than SOR alone ( P  < 0.01). NOB and SOR combination significantly caused much more apoptotic cell death and cell cycle arrest at G0/G1 phase by up-regulation of Bax, Rb1, and CDKN1A levels in PC-3 cells ( P  < 0.01). Therefore, strong synergistic effects between NOB and SOR were analyzed (CI < 1). Conclusion: NOB and SOR combination was more effective than SOR and NOB alone and reduced the exposure time for SOR and NOB in PC-3 cells. Combination strategy is a therapeutic potential to improve efficacy and reduce side-effect of SOR for the treatment of metastatic prostate cancer cells.